Balanced Eating Between Fast Food and Healthy Food for Better Nutritional Needs - Nabilah Nur Kamilah; Asep Bayu Dani Nandiyanto (Universitas Pendidikan Indonesia (UPI), 2024)
This study aims to determine the knowledge and understanding of elementary school students about nutritious food and fast food, as well as recommendations for balancing them. The method used is a quantitative method with an experimental research design. The intended target is elementary school students in grade 5. The subject is 20 students in one class. The research was carried out in 3 stages, (i) pre-test, (ii) education using lecture and picture methods about fast food and healthy food, and the last one was (iii) post-test were the questions given were the same questions as the pre-test. After being educated about healthy nutritious food and fast food, the results showed quite different results from the previous results, which increased by 9% from 71.25 to 81.25%. The ineffectiveness of this method was influenced by the pretest scores of respondents which are already large enough. Thus, the increase is not so large. With the results obtained from the research that has been carried out, it is hoped that school-age children can be better informed about the importance of a balanced intake of healthy food and fast food consumed by children.